The Effectiveness of Law Enforcement on the Crime of Abortion Performed by Underages - Ni Nyoman Alit Meilinda Suasthi; I Nyoman Putu Budiartha; I Nyoman Gede Sugiartha (Warmadewa Press, 2023)
Abortion by minors is prohibited by law, as stipulated in Law Number 35 of 2009 concerning Health under Article 75. Criminal liability for children typically involves punishment or laws that impose penalties equivalent to half of those for adult offenders. Non-criminal abortion is addressed in Article 75, Paragraph 2 of Law Number 35 of 2009 concerning Health, but it mandates counseling or guidance by the authorities before the procedure. In terms of law enforcement effectiveness regarding abortion committed by minors, it involves an investigative process where thorough investigation is conducted by authorities to ensure a fair trial and impose penalties or sanctions that serve as deterrents. The empirical method with an empirical juridical approach utilizing legal concepts and theories is employed in this study. Data for this research is obtained from various literature sources, including legislative regulations and relevant books corresponding to the research title. The study results indicate that while minors are subject to sanctions in compliance with laws and regulations, they are also entitled to government protection as they are deemed legally incompetent and under parental supervision.